2009
DOI: 10.1158/1055-9965.epi-09-0936
|View full text |Cite
|
Sign up to set email alerts
|

Passive Smoking and Risk of Breast Cancer in the California Teachers Study

Abstract: Background: Although recent reviews have suggested active smoking to be a risk factor for breast cancer, the association with passive smoke exposure remains controversial. This risk association was explored in a large prospective study of women, the California Teachers Study. Methods: Detailed lifetime information on passive smoke exposure by setting (home, work, or social) and by age of exposure was collected in 1997 from 57,523 women who were lifetime nonsmokers and had no history of breast cancer. In the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 40 publications
3
59
2
2
Order By: Relevance
“…Smoke from a spouse or the workplace in this study indicates that these two factors are important sources of breast cancer risk in Thai women. The result is consistent with Western women but different in level of exposure (Luo et al, 2011;Reynolds et al, 2009). The immediate implication is that there should be a strong focus on preventing smoke exposure.…”
Section: And the Statistical Comparison Between Two Groupssupporting
confidence: 75%
“…Smoke from a spouse or the workplace in this study indicates that these two factors are important sources of breast cancer risk in Thai women. The result is consistent with Western women but different in level of exposure (Luo et al, 2011;Reynolds et al, 2009). The immediate implication is that there should be a strong focus on preventing smoke exposure.…”
Section: And the Statistical Comparison Between Two Groupssupporting
confidence: 75%
“…As the comprehensiveness of the passive smoking measures has been shown to have a major impact on the magnitude of the passive smoking effect observed, 4,7,8,14,17 the measures of passive smoking exposure available in the EPIC cohort are likely to have underestimated risk associated with passive exposure and might also have diluted the active smoking risks, if some passive smokers were incorrectly classified as "unexposed." Indeed, cohort studies with better passive smoking exposure measure observed higher risk estimates in the most passively exposed women 8,23 and higher risks were also observed in premenopausal women than in postmenopausal women in studies where lifetime exposure to passive smoking was considered. 4 In the EPIC study, the evaluation of the risk in premenopausal women was limited by the small number of cases in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…When only residential exposure was available, little effect of passive smoking was shown. 19,26 When both lifetime occupational and residential exposures 23 or more quantitative measures of passive smoking exposures 8 were evaluated, an increased risk was observed. The results published on data from the Nurses' Health Study, however, did not show any increased risk with passive smoking exposure either at work or at home, but their evaluation of passive smoking exposure remained incomplete.…”
Section: Epidemiologymentioning
confidence: 99%
“…[1][2][3][4][5] Although cigarette smoke is most often associated as a caustive agent in human lung cancers, it also clearly has pervasive systemic effects. For example, cigarette smoke increases the risk for the development of many different types of human cancers, including head and neck, bladder, pancreatic, stomach, liver, ovarian, colon, prostate and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cigarette smoke increases the risk for the development of many different types of human cancers, including head and neck, bladder, pancreatic, stomach, liver, ovarian, colon, prostate and breast cancers. [1][2][3][4][5] During the 20 th century, it has been estimated that tobacco use contributed significantly to the premature deaths of nearly 100 million people world-wide, and it is Cigarette smoke has been directly implicated in the disease pathogenesis of a plethora of different human cancer subtypes, including breast cancers. the prevailing view is that cigarette smoke acts as a mutagen and DNA damaging agent in normal epithelial cells, driving tumor initiation.…”
Section: Introductionmentioning
confidence: 99%